Gibraltar Neanderthals and results of recent excavations in Gorham's, Vanguard and Ibex Caves - Barton, R.N.E
In December 1998, we presented a Special section on great finds and publications of 1848. The discovery of the Gibraltar skull was in that famous year. Now, 150 years later new excavations and a recent conference have once again focused interest on this, the first place where Neanderthal remains were found.